Effect of Njavara (Red) Rice Bran on Physico-chemical, Sensory and Textural Properties of Sweetened Yoghurt: Njavara (Red) rice bran fortified sweetened yoghurt - Thomas, Elizabeth; Ritika; Panjagari, Narender Raju (Indian Journal of Dairy Science, 2024)
Njavara (red) rice and rice bran possess numerous therapeutic applications, including their utilization in treating diabetes, cervical spondylitis, rheumatoid arthritis, neuromuscular diseases, psoriasis, skin lesions, and stomach ulcers. Recently, there has been a notable surge in the attention given to fortifying yoghurt with dietary fiber. This can be attributed to the growing awareness among consumers regarding the correlation between nutrition and health, leading to an increased emphasis on personal well-being. Therefore, to improve the health properties of sweetened yoghurt containing 10% sugar, Njavara rice bran was added in amounts ranging from 0% to 10%. The impact of these additions on the quality of the product, specifically in terms of physicochemical properties, sensory qualities, and texture, was evaluated. Standard method was followed for the preparation of rice bran fortified sweetened yoghurt. The addition of rice bran was found to have a significant impact on the physico-chemical characteristics of sweetened yoghurt. An increase in rice bran was associated with a decrease in yoghurt's titratable acidity. Conversely, the yoghurt's syneresis, water activity, and antioxidant activity were found to increase. Furthermore, the inclusion of rice bran in the yoghurt formulation resulted in a reduction in lightness and an increase in redness values. The addition of increasing quantities of rice bran (7% and 10%) was found to have an impact on the sensory and textural properties of the yoghurt. Based on the results obtained in the present study, it was concluded that acceptable quality sweetened yoghurt could be prepared using rice bran at a 5% level of fortification.